Common fixed point theorems in Menger spaces - Chi-Ming Chen; Tong-Huei Chang (International Journal of Mathematics and Mathematical Sciences)
We proved two common fixed point theorems for four self-mappings and two set-valued mappings with φ-contractive condition in a Menger space.